Rule of Islamic Law dan Mekanisme Penambahan Kewenangan Constitutional Complaint Mahkamah Konstitusi - Anggar Putra (CV. Creative Tugu Pena, 2024)
The Constitutional Court is the guardian of the constitution, the final interpreter of the constitution, the protector of human rights, the protector of the citizen's constitutional rights), protector of democracy (the protector of democracy). These five authorities place the Constitutional Court as the sole guardian of citizens' constitutional rights which are comprehensively explained in the law. The Constitutional Court as the enforcer of